1990
DOI: 10.1071/ar9900289
|View full text |Cite
|
Sign up to set email alerts
|

Gluten polypeptides as useful genetic markers of dough quality in Australian wheats

Abstract: Seed proteins of 28 Australian bread wheat cultivars were analysed by gel electrophoresis to indicate variations in the composition of their gliadins and glutenin polypeptides (both low- and high-molecular-weight). Composition was indicated according to allelic blocks of genes for each protein class and for each chromosome involved. Relationships were studied between gluten-protein alleles, pedigrees and dough properties (in the Extensograph). Overall, gliadins and low-molecular-weight (LMW) subunits of gluten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
52
0
6

Year Published

1997
1997
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(58 citation statements)
references
References 20 publications
0
52
0
6
Order By: Relevance
“…LMW glutenins comprise about 40% of the total endosperm proteins and 60-70% of glutenins. As the major components of wheat storage proteins, LMW-GS fractions have been found to be significantly correlated with dough extensibility (Gupta et al 1989;Metakovsky et al 1990), dough-mixing time (Sissons et al 1998) and dough strength (Tanaka et al 2005). In the past several decades, however, there have been fewer structure and function studies of LMW-GSs compared with HMW-GSs because of the similar mobilities of a large number of subunits in SDS-PAGE analysis and the difficulty of separation and characterization.…”
mentioning
confidence: 99%
“…LMW glutenins comprise about 40% of the total endosperm proteins and 60-70% of glutenins. As the major components of wheat storage proteins, LMW-GS fractions have been found to be significantly correlated with dough extensibility (Gupta et al 1989;Metakovsky et al 1990), dough-mixing time (Sissons et al 1998) and dough strength (Tanaka et al 2005). In the past several decades, however, there have been fewer structure and function studies of LMW-GSs compared with HMW-GSs because of the similar mobilities of a large number of subunits in SDS-PAGE analysis and the difficulty of separation and characterization.…”
mentioning
confidence: 99%
“…Gliadin electrophoresis offers advantages in evaluating wheat genetic resources in comparison to DNA molecular markers, as it is cheaper and less labour intensive to detect the polymorphism. For these reasons, several studies have analysed genetic gliadin polymorphism of wheat collections, mainly of common wheat, from different countries (Metakovsky et al 1990(Metakovsky et al , 1994(Metakovsky et al , 2000Kudryavtsev et al 1996;Metakovsky and Branlard 1998). These studies have indicated that gliadin alleles are very efficient molecular markers to be applied in genetic analysis and to trace out genealogies of wheat cultivars.…”
Section: Introductionmentioning
confidence: 99%
“…Peña et al (2004) reported that wheat lines with Glu-D1d and Glu-B3d showed the strongest gluten strength followed by groups possessing Glu-D1d combined with Glu-B3b, Glu-B3f and Glu-B3g. Glu-D3b allele showed stronger dough strength than Glu-D3a and Glu-D3c in Australian and New Zealand cultivars (Gupta et al, 1989(Gupta et al, , 1991Metakovsky et al, 1990;Luo et al, 2001). However, Branlard et al (2001) reported that Glu-D3a positively affected dough strength in French wheat and Vawser et al (2002) reported that no difference was found in dough strength at Glu-D3 locus.…”
Section: Allelic Variations Of Gluteninmentioning
confidence: 97%
“…Australian researchers proposed that Glu-A3b and Glu-A3d alleles showed stronger dough strength than other alleles (Gupta et al, 1989(Gupta et al, , 1991Metakovsky et al, 1990;Vawser et al, 2002). The rankings of Glu-A3 alleles to dough strength were a=d=f≥e in French wheat cultivars and d>c=e alleles in New Zealand wheat cultivars Luo et al, 2001).…”
Section: Allelic Variations Of Gluteninmentioning
confidence: 99%